Use of concept maps for problem-solving in engineering - Sarker, Prabir (World Institute for Engineering and Technology Education, 2015)
This article presents a study on the use of concept maps as a learning tool for solving problems in engineering. Solving problems of structural analysis needs clear understanding of the fundamental concepts of the method and their links. Concept maps were used in lectures to explain the application of the concepts in solving problems and students were engaged in construction of concept maps before the actual calculations. Anonymous feedback was collected from students on the usefulness of concept maps in their learning. The responses show that the majority of the students found concept maps helpful in understanding the key concepts and their associations in solving problems. It helped students choose the right method from different options in solving a problem. Though the number of students constructing their own concept maps outside the classroom was relatively low, they wanted to see continued use of concept maps since it provoked the thinking process, and helped deep and meaningful learning. Thus, the use of concept maps facilitated student engagement in the classroom, helped solving problems and improved learning in the unit.